2016
DOI: 10.1590/s1806-92902016000700006
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of baled rice straw for ruminant feed

Abstract: -The objectives of this study were to evaluate the effects of cultivation and hay making factors on chemical composition, protein fractionation, and digestibility in rice straw, as well as to identify the chemical fractions that contribute to the variation in its nutritional value for ruminants. Statistical procedures were performed in a model that included rice crop cycle, sowing season, baling season, soil classification, fertilizer application, and productivity (kg/ha) as fixed effects and the hay bale as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
3
6
0
2
Order By: Relevance
“…Crude protein is generally considered a good determinant of forage quality. The low CP values of 30-50 g/kg reported in the current study (Table 1) are consistent with a number of previous studies (Sophal et al, 2010;Rahman et al 2010;Peripolli et al, 2016;Singh, 2016;Ganai et al, 2017), but lower than the 50-80 g/kg reported by Dong et al (2013) and fall short of the 110-130 g/kg recommended for ruminant maintenance diets (National Research Council (NRC), 2007). Results of this study also showed that per growing and baling year, Angola straw had the highest CP content, while the late maturing SUPA rice had the lowest CP content.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Crude protein is generally considered a good determinant of forage quality. The low CP values of 30-50 g/kg reported in the current study (Table 1) are consistent with a number of previous studies (Sophal et al, 2010;Rahman et al 2010;Peripolli et al, 2016;Singh, 2016;Ganai et al, 2017), but lower than the 50-80 g/kg reported by Dong et al (2013) and fall short of the 110-130 g/kg recommended for ruminant maintenance diets (National Research Council (NRC), 2007). Results of this study also showed that per growing and baling year, Angola straw had the highest CP content, while the late maturing SUPA rice had the lowest CP content.…”
Section: Discussionsupporting
confidence: 92%
“…The highest hemicellulose content was recorded in IRGA 418 and Angola rice straws and this was lower than the 260-333 g/kg DM reported in Brazil (Peripolli et al, 2016), but similar to the 190-250 g/kg reported in India (Malik et al, 2015). Compared to a study in India (Yoswathana & Phuriphipat, 2010), the average cellulose content of rice straw in this study was lower, while the ADL was comparable.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that the nutritional value of paddy straw is lower than alfalfa hay and is a highly lignified material 14 . There is a perception that milk and milk products derived from cows reared in the grazing system are natural and healthier, and hence have high demand in the dairy market 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian yang dilakukan oleh santos et al (2010) dan Peripolli et al (2016) menunjukkan bahwa nilai nutrisi dari jerami sangat bervariasi. Variasi tersebut kemungkinan disebabkan oleh siklus panen, jumlah produksi beras yang dihasilkan dan waktu pengemasan.…”
Section: Nilai Nutrisi Jeramiunclassified